PERKEMBANGAN PSIKOMOTORIK PADA ANAK USIA DINI - Maghfiroh; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This article discusses psychomotor development at an early age where psychomotor development is the development of controlling body movements through coordinated activities between the central nervous system and muscles. Starting from rough movements. This article aims to find out what characteristics are related to the psychomotor development of early childhood and the factors that influence psychomotor growth in early childhood.